EMU and ECB Conflicts - William Mackenzie (Journal of European Public Policy, 1997)
EMU is based on several principles including independence of the Central Bank (ECB) which has as its main objective the control of inflation, external co-ordination of budgetary policies with the common monetary policy and finally the framing of fiscal policy by prudential ratios. This type of organization is also proposed for the transitional phase of the Single Market. This institutional framework is problematic because it does not define the internal co-ordination and external economic policies and because it does not raise the issue of coherence between economic policies although it implicitly suggests what is contradictory with these two requirements is the management of the inflation-unemployment dilemma which is affected the Central Bank and the public debt dilemma management-rate real interest which is affected by the state. This article examines these tensions and proposes solutions.
Keywords: F15; 330; EMU; ECM